High Nonlinearity and Single-Mode Transmission in Tapered Multimode <tex Notation="TeX">$\hbox{As}_{2}\hbox{Se}_{3}$</tex> -PMMA Fibers - Chams Baker; Martin Rochette (IEEE Photonics Journal, 2012)
We demonstrate the fabrication and use of a 10-cm-long-PMMA microwire with ultrahigh waveguide nonlinearity γ= 176 W-1 m-1 that is fully compatible with standard single-mode silica fibers. The fabrication of this microtaper is simplified with respect to a previous approach as the core is made of a bulk cylinder rather than a single-mode step-index fiber. The successful operation of this nonlinear component is demonstrated with a Kerr-shutter switching experiment based on nonlinear polarization rotation.